Educational reform, ability and family background - Costas Meghir; Mårten Palme (Institute for Fiscal Studies (IFS), 2004)
In this paper we evaluate the impact of a major school reform, that took place in the 1950s in Sweden, on educational attainment and earnings. The reform, which has many common elements with reforms in other European countries including the UK, consisted of increasing compulsor schooling, imposing a national curriculum and abolishing selectionby ability into Academic and non-academic streams at the age of 12 (comprehensive school reform). Our data combines survey data with administrative sources. We find that the reform increased both the educational attainment and the earnings of children whose fathers had just complusory education. However the earnings of those with educated parents declined - possibly because of a dilution of quality at the top end of the education levels. The overall effect of the reform was however positive.
Keywords: H52; I21; I28; J24; J31; 330; Human capital; evaluation of education reform; comprehensive schools; compulsory schooling; earnings; administrative data; differences in differences; Schulpolitik; Bildungsreform; Bildungsertrag; Schweden